Editorial - Oniwide, Oyetola Olaoluwa (NIU Journal of Humanities; Vol 10 No 1 (2025): NIU Journal of Humanities, Vol. 10 No. 1, March 2025DO - 10.58709/niujhu.v10i1.2094, 2025)
This edition of NIU Journal of Humanities touches on Development Administration, Educational Psychology as well as Language and Literary Studies. The first part of the Journal focuses on Development Administration. Using Nigeria’s 2023 Presidential Election as a case study, one of the papers in this section empirically argues that ethnicity significantly influenced voter decisions and highlights the challenges posed by ethnic-driven voting patterns. To mitigate the negative effects of ethnic polarization in elections, the study recommends targeted civic education initiatives led by the Nigerian government, the National Orientation Agency (NOA), and educational institutions. Implementing a civic education curriculum that fosters national unity and encourages policy-driven electoral choices will be critical to strengthening democratic process. Papers in the second section are on Educational Psychology. Using Secondary School Students in Lagos State, Nigeria as case studies, one of the papers in these sections argues theoretically and demonstrates empirically that there is a significant relationship between formative evaluation feedback and students' academic achievement in Economics. It is therefore recommended that school teachers should acquire updated skills and best practices in using diagnostic evaluation to enhance students' academic performance, not only in Economics but across all subjects. One of the papers, in the last section on Language and Literary Studies, examines the roles of musical artistes who use their songs as a tool for protest and activism against the government. The study is anchored on the theory of relative derivation, which is defined as the perceived lack of resources required to maintain quality life in a society.